POLÍTICAS MUNICIPAIS DE GERAÇÃO DE RENDA: POSSIBILIDADES DE ENFRENTAMENTO AO DESEMPREGO - Pedersen, Jaina R.; Carvalho, Clara C. B. d.; Tôndolo, Cássio E. D. S.; Silva, Jorge A. d.; Andrade, Maria M. P. D. (Salão do Conhecimento, 2013)
Resumo